The relationship between work and family conflict with stress among civil servants - Hassan, Mohammad Mujaheed; Mohd Narahim, Muhammad Daniel Aidil; Md Noor, Amna; Mohd Khir, Azlina; Wan Abdullah, Wan Arnidawati (Secholian Publication, 2022)
This study aims to examine the relationship between work conflict and family conflict against stress among civil servants at the South Klang District Police Headquarters, Selangor, Malaysia. The survey questions used were Perceived Stress Scale -10 (PSS-10) andWork-Family Conflict. Pearson correlation analysis showed that there was a significant negative relationship between work conflict and family conflict with stress. This study has confirmed that work conflicts and family conflicts can influence stress among respondents coinciding with the results of a significant relationship between work conflicts and family conflicts with stress. The results of the study also found significant differences between work conflicts on gender, work conflicts and stress on income. Meanwhile, the family conflict shows a significant difference in the total number of children. Based on the findings of the study, researchers have discussed some suggestions for future research.